Radioprotective Properties of Fullerenol: Cellular, Biochemical and Physicochemical Approaches - Kolesnik, O.V.; Grabovoy, A.S.; Badun, G.A.; Churilov, G.N.; Kudryasheva, N.S. (Karagandy University of the name of acad. E.A. Buketov, 2024)
The search for optimal radioprotective methods and tools under low-dose radiation exposures represents a pressing issue in the field of modern radioecology. The objective of the study was to investigate the radioprotective properties of fullerenol C60,70Oy(OH)x, (x+y = 24–28), a water-soluble polyhydroxylated fullerene derivative with an electron-deficient aromatic carbon structure. Tritium, a radionuclide of low decay energy, was selected to simulate an exposure to low-dose irradiation (< 0.05 Gy). We applied luminous marine bacteria Photobacterium phosporeum as a model cellular object to monitor radiation bioeffects; the bioluminescence intensity of the bacteria was used as a tested biological parameter. Tritium activated the bacterial luminescence; the addition of fullerenol (< 3·10–3 g/L) “mitigated” the activation, thus revealing the radioprotective capacity of fullerenol for the marine microorganism. To evaluate the mechanisms of radioprotection of fullerenol in tritiated water, we investigated the effects of fullerenol on: (1) the content of reactive oxygen species and (2) the intensity of bioluminescence in the bacterial enzymatic reaction. Tritiated water produced moderate deviations from the control values, whereas the addition of fullerene brought these values closer to the “control” ones. All observed effects were attributed to variations in the ionic balance of the aqueous medium, which resulted in the activation of bacterial functions through cell membranes.
Keywords: tritium; fullerenol; radioprotection; luminescence; bacteria; bioassay; enzymes; reactive oxygen species